Transient thermal stress development in direct chill cast ingots with application of a wiper. (4th July 2018) - Wang, Yunbo; Krane, Matthew John M.; Trumble, Kevin P.
ABSTRACT: A full 3D transient model of direct chill casting is developed to predict the thermal stress during the startup phase for AA5182. Simulations show that tensile stress starts to develop at ingot surface and gradually migrates to ingot center. By varying the position of wiper below the mold, the maximum residual stress in the ingot center is reduced by up to 35% compared to that without the use of a wiper. The closer the wiper is inserted below the mold, the larger is the stress reduction effect, but at a greater risk of remelting surfaces below the wiper. In order to prevent this, forced-convection air cooling is recommended on ingot surface below the wiper. The current study recommends application of a moving wiper, from a lower to the bottom of the sump, to combine the benefit of reducing thermal stress and centerline segregation without surface bleeding-out.